Two solvent-stable MOFs as a recyclable luminescent probe for detecting dichromate or chromate anions - Cao, Chun-Shuai; Hu, Huan-Cheng; Xu, Hang; Qiao, Wan-Zhen; Zhao, Bin (CrystEngComm, 2016)
Two unique 2D Zn-MOFs with the formulas {[Zn(btz)] n } ( 1 ) and {[Zn 2 (ttz)H 2 O] n } ( 2 ) were synthesized using in situ generated ligands under hydro(solvo)thermal conditions. Both 1 and 2 exhibit high thermo-stability, solvent-stability and pH-stability. Thermogravimetric analyses (TGA) reveal that 1 and 2 remain intact until about 365 °C and 332 °C, respectively. The samples of 1 and 2 were immersed in twelve common solvents for 24 hours, and the obtained PXRD patterns remain well consistent with the simulated ones. They were immersed in a series of solutions with pH values ranging from 1.0 to 14.0 for five hours, and the PXRD patterns of these samples remain unchanged spanning the pH range of 1-13. The luminescence investigations reveal that the compounds 1 and 2 can efficiently and selectively detect Cr 2 O 7 2− or CrO 4 2− among twenty-one anions. Importantly, they can be regenerated by a fast and simple method in detecting Cr 2 O 7 2− or CrO 4 2− . Two unique 2D Zn-MOFs with high thermo-stability, solvent-stability and pH-stability can efficiently and selectively detect Cr 2 O 7 2− /CrO 4 2− among twenty-one anions. Importantly, they can be regenerated by a simple and rapid method in detecting Cr 2 O 7 2− /CrO 4 2− .